Bacteria from an oil palm agricultural system and their interactions with Ganoderma boninense and Trichoderma harzianum - Abdullah, Faridah; Rush, Mohd. Hefni; Sebran, Noor Haida (Universiti Putra Malaysia Press, 2005)
The fungus Trichoderma harzianum (isolate FA 1132) has shown potential as a biological control agent of the oil palm pathogen, Ganoderma boninense. It is currently being produced on a large scale as Trichoderma-infused compost for field trials. This study isolated bacteria from such a compost as well as from oil palm rhizospheres. They were screened for antagonistic reactions with FA 1132. Four out of six species of bacteria showed fungistatic activity towards G. boninense. Corynebacterium urealyticum gave the highest percentage inhibition of radial growth (PIRG) at 86.6%, but was incompatible with FA 1132. Except for C. urealyticum, all the other isolates showed compatiblity with FA 1132. This study deduced that Chromobacterium violaceum and Burkholderia cepacia may have the capacity to act as individual inoculants to inhibit the growth of G. boninense, as well as have the potential to be used as co-inoculants in consortium with T. harzianum FA 1132, for enhanced performance in a biological control formulation.